RNA-Based Therapeutics: Current Developments in Targeted Molecular Therapy of Triple-Negative Breast Cancer - Sakib Haque; Kiri Cook; Gaurav Sahay; Conroy Sun (MDPI AG, 2021)
Triple-negative breast cancer (TNBC) is a highly heterogeneous and aggressive cancer that has the highest mortality rate out of all breast cancer subtypes. Conventional clinical treatments targeting ER, PR, and HER2 receptors have been unsuccessful in the treatment of TNBC, which has led to various research efforts in developing new strategies to treat TNBC. Targeted molecular therapy of TNBC utilizes knowledge of key molecular signatures of TNBC that can be effectively modulated to produce a positive therapeutic response. Correspondingly, RNA-based therapeutics represent a novel tool in oncology with their ability to alter intrinsic cancer pathways that contribute to poor patient prognosis. Current RNA-based therapeutics exist as two major areas of investigation-RNA interference (RNAi) and RNA nanotherapy, where RNAi utilizes principles of gene silencing, and RNA nanotherapy utilizes RNA-derived nanoparticles to deliver chemotherapeutics to target cells. RNAi can be further classified as therapeutics utilizing either small interfering RNA (siRNA) or microRNA (miRNA). As the broader field of gene therapy has advanced significantly in recent years, so too have efforts in the development of effective RNA-based therapeutic strategies for treating aggressive cancers, including TNBC. This review will summarize key advances in targeted molecular therapy of TNBC, describing current trends in treatment using RNAi, combination therapies, and recent efforts in RNA immunotherapy, utilizing messenger RNA (mRNA) in the development of cancer vaccines.